Identification and characterization of mature β-hexosaminidases associated with human placenta lysosomal membrane. Issue 4 (10th September 2008) - Magini, Alessandro; Mencarelli, Simona; Tancini, Brunella; Ciccarone, Virginia; Urbanelli, Lorena; Hasilik, Andrej; Emiliani, Carla
Abstract : Hex (β-hexosaminidase) is a soluble glycohydrolase involved in glycoconjugate degradation in lysosomes, however its localization has also been described in the cytosol and PM (plasma membrane). We previously demonstrated that Hex associated with human fibroblast PM as the mature form, which is functionally active towards GM2 ganglioside. In the present study, Hex was analysed in a lysosomal membrane-enriched fraction obtained by purification from highly purified human placenta lysosomes. These results demonstrate the presence of mature Hex associated with the lysosomal membrane and displaying, as observed for the PM-associated form, an acidic optimum pH. When subjected to sodium carbonate extraction, the enzyme behaved as a peripheral membrane protein, whereas Triton X-114 phase separation confirmed its partially hydrophilic nature, characteristics which are shared with the PM-associated form of Hex. Moreover, two-dimensional electrophoresis indicated a slight difference in the pI of β-subunits in the membrane and the soluble forms of the lysosomal Hex. These results reveal a new aspect of Hex biology and suggest that a fully processed membrane-associated form of Hex is translocated from the lysosomal membrane to the PM by an as yet unknown mechanism. We present a testable hypothesis that, at the cell surface, Hex changes the composition of glycoconjugates that are known to be involved in intercellular communication and signalling.